Menemukan Ketenangan di Masjid : Perspektif Keamanan Spiritual bagi Masyarakat Muslim - Annisa Dama Yanti Samoeri; Indah Mutia; Nailah Assahira; Muhammad Rafi Dhaifullah; Wismanto Wismanto (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
Mosques have a very important role in the lives of Muslims, not only as places of worship, but also as a source of spiritual security. As centers of religious activity, mosques provide a conducive environment for the development of faith and piety. In this context, the mosque functions as a protector from negative influences that can disrupt the spiritual stability of individuals and communities. This research aims to examine the function of mosques as places of spiritual security. In the midst of the onslaught of information and moral challenges facing modern society, mosques are the first fortress that protects people from destructive influences. In it, pilgrims can find calm and peace, as well as strengthen social ties between community members. Worship activities, recitations and religious discussions in mosques contribute to deepening spiritual and moral understanding. Through a qualitative approach using heritage study methods, this research explores the role of mosques as places of spiritual refuge which is also reflected in the practice of congregational prayer. This activity not only strengthens a sense of togetherness, but also builds discipline in worship. This discipline is important for forming an individual's character of obedience and integrity, making him more resistant to worldly temptations. The research results show that the mosque functions as a place of education and dissemination of Islamic values. Through educational and da'wah programs, mosques can create awareness of the importance of morality and ethics in everyday life. This functions as a shield against deviant behavior that can threaten societal harmony.